Women Marginalization as Victims of Sexual Harassment: Corpus-Assisted Critical Discourse Analysis - Prastitasari, Maydita Piety; Tobing, Roswita Lumban (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
This study aims to explain the subject-object position and readers’ position in reporting on women as victims of sexual harassment that were built by mass media Detik.com. The design of this study is descriptive-qualitative study. The data of this study are all e-news about sexual harassment cases which published by Detik.com starting 1st January to 31st December 2021. Data was collected by using corpus-based method and corpus tools (SketchEngine and AntConc) as research instrument. Data, then, was analyzed using the CACDA or the combination of corpus linguistic and critical discourse analysis. The results of this study are: (1) ‘the police’ were more dominantly positioned as subjects in the news report (4 datas), while the most dominant position of the object is occupied by the ‘the perpetrator of sexual harassment’ (4 datas). 3 datas, among all 5 datas, marginalized women as the victims of sexual harassment through the word construction, whereas the other 2 datas showed the author’s side with the victims. (2) on 1 data, the authors combined the mediation and cultural code processes, while on 4 other datas the authors used only the mediation process. Though most of the the readers’ comments were accusing and blaming the perpetrator, yet some of them still marginalized women. The novelty of this study is the implementing Sara Mill’s critical discourse analysis on CACDA method.